Peculiarities of Usage of Phraseological Units in German Newspaper Text: Gender Aspect - Задорожна, Ірина Петрівна; Коломийська, Іванна Андріївна (Studien zur deutschen Sprache und Literatur, 2021)
The article is devoted to a comprehensive study of peculiarities of usage of phraseological units in German newspaper text depending on gender factor. Special attention has been paid to the analysis of quantitative characteristics. The influence of the gender factor on the processes of modification of phraseological units has been observed. With the help of linguistic statistic methods (criterion χ2 and Chuprov’s contingency coefficient K) statistically significant quantitative differences in the usage of phraseological units by both sexes have been determined. The results of investigation conducted on the material of the Internetversions of two most popular German newspapers Die Zeit and Süddeutsche Zeitung have revealed quantitative differences in the usage of phraseological units by the two sexes mainly in “one-gender” speech. In “two-gender” speech the tendency to relative equality of communicators of both sexes has been observed. Among the phraseological units used in newspaper articles there is a group of units which is characterised by extremely high frequency of usage (hyper frequent) and which comprises “absolutely masculine”, “absolutely feminine”, “relatively masculine”, “relatively feminine” and “gender indifferent” phraseological units. The processes of expansion and substitution have proved to be the most noticeable changes in the structure of both male and female phraseological usages. Significance of usage of elliptical phraseological constructions in “one-gender women” articles has also been statistically proved. Differences that exist in “one gender” newspaper article show that communication, namely its speech expression, depends upon the gender identity of both communicants.
Keywords: Phraseological unit, frequency of usage, gender, German newspaper text, modification